#63: Antibodies to Peptides Representing Plasmodium falciparum Circumsporozoite Protein Reflect Acquisition of Naturally Acquired Immunity in Malian Adults and Children. (26th March 2021) - Friedman-Klabanoff, DeAnna J; Travassos, Mark A; Agrawal, Sonia; Ouattara, Amed; Pike, Andrew; Bailey, Jason A; Adams, Matthew; Coulibaly, Drissa; Lyke, Kirsten E; Laurens, Matthew B; Takala-Harrison, Shannon; Kouriba, Bourema; et al.
Abstract: Background: An effective vaccine against Plasmodium falciparum, the most common and deadly cause of malaria, is a global priority. Circumsporozoite protein (CSP) is a major P. falciparum vaccine target. Previously recognized CSP epitopes include the immunodominant NANP repeat region, the conserved junction between Region 1 (R1) and the NANP repeats, and the polymorphic Th2R and Th3R in the C-terminus. RTS, S, the most advanced vaccine to date, contains 19 NANP repeats and the C-terminus from the 3D7 parasite clone. CSP-specific monoclonal antibodies to the R1-NANP junctional region showed potent neutralizing activity in vitro and in vivo and are therefore under development for immunoprophylaxis. However, little is known about naturally acquired humoral immunity to precise and diverse epitopes along the CSP sequence, especially in the R1-NANP junctional region. Our goal was to use novel high-throughput tools to examine immunity to diverse CSP epitopes. Methods: We probed sera from 10 adults and 10 children from Bandiagara, Mali, a region with intense, seasonal malaria transmission, on a diversity-reflecting peptide microarray. This microarray included 73 CSP variants from reference genomes and field-derived genomic data represented as 16 amino acid (aa) peptides with 12 aa overlap. We used a sliding window-based average smoothing procedure to determine log2 transformed signal intensities (SI) at each aa position. SI and serorecognition, defined as SI >2.5 standard deviations above the mean SI of malaria-naïve controls, were compared. We used the Wilcoxon rank-sum test for comparisons between adults and children and the Wilcoxon signed-rank test for matched comparisons of children over the malaria season, with the Benjamini-Hochberg procedure to control the false discovery rate. Results: Adult sera recognized more variants than children at 313 of the 401 positions along CSP, including areas of the R1-NANP junctional region, the NANP repeat region, and the C-terminal Th2R and Th3R epitopes. Adults had higher SI than children to variants in known epitopes, including the R1-NANP junctional region and NANP, but not to a large portion of the 3D7 sequence of Th2R. Across the malaria season, children did not recognize significantly more variants at any one position. However, children had higher SI mid-season when compared with pre-season at a few small epitopes in the R1-NANP junctional region and Th2R. No significant differences existed between SI at any position when comparing post- to mid- or pre-season. Conclusions: We identified precise CSP epitopes where serologic responses differed between adults and children and in children over a malaria season in Bandiagara. Adults showed responses to more variants and higher antibody responses at the R1-NANP junctional region and the NANP repeat region, but not to the 3D7 variant sequence in the Th2R epitope, which is included in RTS, S. Children acquired some short-lived immunity to the R1-NANP junctional region and a Th2R epitope during the season but not the NANP repeat region. Our limitations included a small sample size. Next steps include differentiation of immunodominant from protective responses in a larger study with longitudinal infection surveillance data.